Clinicopathologic Characterization of Epithelioid Hemangioendothelioma in a Series of 62 Cases: A Proposal of Risk Stratification and Identification of a Synaptophysin-positive Aggressive Subset. (May 2021) - Shibayama, Takahiro; Makise, Naohiro; Motoi, Toru; Mori, Taisuke; Hiraoka, Nobuyoshi; Yonemori, Kan; Watanabe, Shun-ichi; Esaki, Minoru; Morizane, Chigusa; Okuma, Tomotake; Kawai, Akira; Ushiku, Tetsuo; et al.
Abstract : Epithelioid hemangioendothelioma (EHE) is a rare vascular endothelial neoplasm with characteristic histology and distinctive fusion genes. Its clinical presentation and outcome are heterogeneous, and the determinants of survival are controversial. In this study, we aimed to identify clinicopathologic prognostic factors of EHE in a retrospective cohort of 62 cases with CAMTA1/TFE3/WWTR1 alterations. The tumors were of the CAMTA1 subtype for 59 cases, TFE3 subtype for 2 cases, and variant WWTR1 subtype ( WWTR1-ACTL6A ) for 1 case. Twenty-two tumors (35.5%) demonstrated atypical histology, defined by having at least 2 of the following 3 findings: high mitotic activity (>1/2 mm 2 ), high nuclear grade, and coagulative necrosis. During a median follow-up of 34 months, 11 patients (18%) died, and the 5-year overall survival rate was 78.8%. Survival did not correlate with such clinical parameters as age, sex, tumor sites, multifocality, and multiorgan involvement. Conversely, based on both univariate and multivariate analyses, large tumor size (>30 mm) and histologic atypia were significantly associated with a shorter survival. A proposed 3-tiered risk assessment system using these 2 parameters significantly stratified the patients into low-risk, intermediate-risk, and high-risk groups with 5-year overall survival rates of 100%, 81.8%, and 16.9%, respectively ( P <0.001). Four tumors (6.4%) expressed synaptophysin, which all belonged to the high-risk group and pursued an aggressive course. The present study demonstrated the independent prognostic significance of large tumor size and atypical histology in EHE, as well as the value of risk stratification using these 2 factors. Moreover, we revealed a small EHE subset with aberrant synaptophysin expression, which may have potential prognostic and diagnostic implications. Abstract : Supplemental Digital Content is available in the text.